Large sporadic abdominal wall desmoid tumor due to repeated caesarean sections, a rare and long-term unexpected morbidity - Agrawal, Priti; Agrawal, Rishi; Lobo, Anandi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
We present a case of large abdominal wall desmoid tumor (DT) arising due to repeated caesarean sections (CS) in a young woman of reproductive age group and managed with wide resection of tumor and abdominal wall reconstruction (AWR). Our patient was a 30-year-old female, came with complaints of persistent abdominal pain associated with mass on abdominal wall and difficulty in walking for 2 years. Patient had 3 living children, all were delivered by CS. Ultrasonography and CT scan of abdomen with contrast revealed a large solid abdominal wall mass and FNAC was suggestive of benign spindle cell neoplasm. We performed a wide surgical excision of tumor. Abdominal wall reconstruction done with prolene mesh. Post-operative period was uneventful with satisfactory wound healing. DTs are rare tumors that occur anywhere in the body and have quite variable clinical behavior. In our patient this tumor had occurred sporadically about 4-5 years of last child birth. Repeated trauma of surgeries on the abdominal wall led to the catastrophic destruction of the musculature in our patient. In this case CT scan revealed solid lump on abdominal wall without any evidence of incisional or inguinal hernia and associated intraabdominal pathology. Our specimen tested positive for β catenin confirming DT. Surgery remains the main stay of treatment in all patients. In female patients presenting with lower abdominal wall tumor with history of previous CS or gynecological surgeries, DT should be considered.